Microbial flora in patients with bronchopulmonary pathology - Boyko , Valery; Sochnieva, Anastasiia; Tkachenko , Vladimir; Kritsak , Vasyl; Minukhin , Dmytro; Yevtushenko , Denys; Ponomaryov , Volodymyr; Ponomarova , Valeriia (Annals of Mechnikov’s Institute, 2025)
Introduction. The study of microbial pathogens of acute purulent-destructive diseases of the lungs and pleura significantly affects the further course of the disease and the outcome of treatment. The appointment of antibacterial drugs taking into account the sensitivity to the microbial pathogen has a significant advantage compared to broad-spectrum antibacterial therapy. Materials and methods. The results of microbiological studies of tracheobronchial tree and pleural cavity washes in 500 patients with bronchopulmonary pathology for the period 2008-2024 were analyzed. This section of the study was completed by patients who made up the control (238 patients (47.6%) and the main group (262 patients (52.4%) of the study. Results and Discussion. This study provided an idea of ​​the significance of the spectrum of microbial flora of bronchial and pleural washes in patients with bronchopulmonary pathology during different periods of its complex treatment. Conclusions. Studies of microbial flora in patients with bronchopleural diseases reflect specific pathological pathways and can become an important tool for making clinical decisions when managing this complex cohort of patients.